The Urgency of Alternative Regulations Resolution of Disputes Regarding Termination of Employment in Cases of Force Majeure - Kadek Agus Sudiarawan; Ni Made Gina Anggreni; Ni Putu Ayu Meylan Ardini (Universitas Negeri Malang, 2025)
This study aims to analyze termination of employment under force majeure circumstances, the dispute-resolution system based on statutory regulations, and alternative mechanisms that may be implemented to address disputes arising from such terminations. The research employs a normative legal research method with a statutory approach. The findings indicate that termination of employment by companies due to declining revenues leading to financial losses during periods of global crisis, which ultimately result in the temporary or permanent cessation of business operations, satisfies the characteristics of force majeure. The dispute resolution system for termination of employment under Law Number 2 of 2004 may be pursued through three mechanisms, namely bipartite negotiations conducted through deliberation to reach an agreement, tripartite procedures involving a third party through mediation, or adjudication before the Industrial Relations Court. Online dispute resolution, which enables dispute resolution without physical meetings by leveraging internet connectivity and video conferencing technology, represents an alternative model for resolving termination-of-employment disputes arising from force majeure that may be implemented in the future.